Inteligência competitiva organizacional: um modelo apoiado nos comportamentos de busca, compartilhamento e uso de informação e de TIC - Teixeira, Thiciane Mary Carvalho [UNESP] (2014)
The organizational competitive intelligence emerges as a strategic process that converts data, information and knowledge into a competitive advantage for the organization. Is argued about the behavior of seeking, sharing and use of information and information technology and communication should be practiced by managers, because they are fundamental to organizational competitive intelligence process. The problem of research aims to investigate whether the managers practicing and recognize importance the behavior of seeking, sharing and use of information and information and communication technology for the process of organizational competitive intelligence? Relies on the assumption that the process of organizational competitive intelligence should be supported the behaviors of seeking, sharing and use of information and information and communication technology. The starting point is the following guiding principles: 1) the behavior of information seeking and sharing positively influence the prospecting and scanning activities; 2) the information use and information and communication technology use to positively influence decision-making activities and planning of strategic actions. The overall objective of the research aims to identify key practices and measure the degree of importance about the behaviors of seeking, sharing and use of information and information technology and communication in companies awarded in 2012 in Ceará, by means of the Delmiro Gouveia award, in order to propose a conceptual model of organizational competitive intelligence. The methodological procedures adopted to search for qualitative and quantitative nature of the descriptive-explanatory type, whose field research drew on data collection from the application of a questionnaire and an interview. After the analysis and reflection of the data and information obtained, it was possible to develop a conceptual model of organizational competitive intelligence based...